THE THE EFFECT OF BOWEL MASSAGE ON BODY NOISE FREQUENCY IN POST TREPANATION PATIENTS - Galih Pandu Sinaga (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Trepanation is one of the most serious and soul-critical traumas. The main goal of anesthetic management for patients with brain injury is optimization of cerebral perfusion pressure and brain oxygenation. As a result of anesthetic drugs reduce peristalsis in the large intestine and small intestine. Bowel massage is a mechanism of action to reduce contractions and tension in the abdominal muscles, increase motility in the digestive system, increase secretions in the intestinal system and have an effect on sphincter relaxation so that this mechanism of action will facilitate and facilitate expulsion of feces. The universal aim of this research is to identify the comparison of bowel sounds frequency in post trepanation patients between being treated and not being treated in the ICU room at RSUD dr. Saiful Anwar Malang. This study uses a quantitative approach with a Quasi Experimental design with a Non Equivalent Control Group Design approach. The sampling technique used in this research is accidental sampling. Linear regression test between time and bowel sounds in the treatment group obtained a p value of 0.048 (p <0.05), it can be concluded that time has a significant effect on bowel sounds in the treatment group. Test the difference in bowel bissing between the control group with the Mann Whitney test at 3 different times. The p value is (p < 0.05), meaning that there is a difference in bowel sounds after bowel massage.